Reviewing Reservoir Operations: Can Federal Water Projects Adapt to Change? - Benson, Reed D. (Columbia Journal of Environmental Law, 2019)
The Army Corps of Engineers and the Bureau of Reclamation spent much of the twentieth century building large dams that dramatically altered the nation’s rivers. The “big dam era” of federal water policy may have ended decades ago, but the dams that went up in that era are still in place today. These dams form reservoirs that provide a range of benefits including water supply, flood control, and hydropower, and whatever the arguments in favor of taking out some specific ones, few if any major federal dams will be removed anytime soon. Yet each existing dam faces an important question about its future: should it be operated differently than it is now? Every reservoir stores and releases water to serve specific purposes, and an operating plan directs the timing and rate of storage and releases from a particular reservoir. Many federal water projects—dams, reservoirs and associated facilities—have operating plans that are decades old, because the projects were built at least forty years ago and their plans have not been significantly revised since they were fairly new. The Corps and the Bureau, along with existing project beneficiaries, might argue that projects continue to perform just fine under the existing operating plans, and “if it ain’t broke, don’t fix it.” But there are good reasons for the agencies to revisit the old plans, because their reservoirs operate in such a dramatically changing context. First, the area served and affected by a federal water project may have changed greatly since the project was built. Second, the legal and policy context has evolved significantly since the Corps and Bureau built most of their projects. Third, science has advanced significantly, providing better understanding of the positive and negative effects of dam operating practices on the downstream environment. Fourth, climate change has serious implications for dam operating plans. Even before climate change became a front-burner issue in water management, water policy experts were calling for review of water project operations. The Corps and the Bureau, however, rarely revise the operating plans for their dams. Although each agency has its own policies and practices in this regard, neither has a regular program of updating and revising the operating plans for all the dams it manages, and with certain exceptions neither has been eager to revisit the operating plan for a specific dam. Thus, the agencies continue to store and release water from their dams more or less as they have for decades, never officially considering—or providing an opportunity for others to propose—potential changes that could be beneficial. Because of this operational inertia, the Corps and the Bureau are missing an opportunity to adapt their water projects to changes that have already occurred and to prepare for future challenges, especially those posed by climate change. This Article begins by reviewing the purposes for federal water projects, and identifies some of the trade-offs involved in operating projects for certain purposes. It then addresses the legal factors that determine or influence project operations, beginning with project authorizing statutes and ending with federal environmental laws. The Article examines Corps and Bureau policies regarding project operating plans, the reasons for agency reluctance to review and revise their plans, and some of the factors that prompt the agencies to proceed with reviews. It then summarizes periodic review requirements in two analogous contexts—federal land management plans, and hydropower project licenses—and considers the potential significance of these requirements for federal water projects. Finally, the Article examines what the Corps and the Bureau, along with the courts and Congress, are already doing on this issue, and what more they could do to ensure that project operating plans are reviewed and revised. It concludes with some brief observations about why the agencies should proceed with such reviews.